Pengaruh Penerapan Standar Akuntansi Keuangan Terhadap Kualitas Laporan Keuangan Pada Perusahaan Manufaktur - Sri Anawati; Noviyanti . (GLOBAL SCIENTS PUBLISHER, 2026)
Manufacturing companies engage in complex transactions; therefore, strict compliance with Financial Accounting Standards (FAS) is essential to ensure high-quality financial reporting. This study analyzes the impact of the implementation of Financial Accounting Standards on the quality of financial statements in manufacturing companies. Financial statement quality is assessed using the qualitative characteristics of accounting information, namely relevance, reliability, understandability, and comparability. A quantitative research design is employed by distributing structured questionnaires to accounting and finance personnel in manufacturing companies. After conducting validity, reliability, and classical assumption tests, the data are analyzed using simple linear regression. The results indicate that the implementation of Financial Accounting Standards has a positive and statistically significant effect on financial statement quality. These findings suggest that higher compliance with Financial Accounting Standards leads to more reliable financial information that supports decision-making. This study provides empirical evidence that consistent implementation of accounting standards enhances financial reporting quality and offers practical implications for manufacturing companies seeking to improve transparency and accountability in financial reporting.